The Influence of Certification on Teachers’ Motivation and Teachers’ Performance - Purwanti, Ana; Zarger, Azhar Amin (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to analyze the effect of teacher’s certification on work motivation and performance of elementary school teachers in Mesuji Regency. The study was conducted using a survey method. Data collection through questionnaires and analyzed using multiple linear regression. The survey results showed that teacher’s certification had a significant positive effect on teacher’s performance, where an increase in certification of one unit can increase performance by up to 30.7%. In addition, work motivation also made a significant contribution, with a performance increase of 46.2%. When applied simultaneously, both certification and work motivation showed a strong influence on teacher’s performance, with a regression coefficient value of 47.1%. The implications of this study indicate the need for integrated professional development, where increasing teacher’s certification must be balanced with programs that can increase work motivation. Education policies need to pay attention to both aspects to create a quality learning environment and support the development of teacher competencies in a sustainable manner.